A VISUAL GRAPHIC BASED MODELING FRAMEWORK OPTI-BLEND FOR INTEGRATED CODE ANALYSIS - Patil, Tulshihar; Joshi, Shashank; Prabhakar, AY; Suryawanshi, Akash; Talegaonkar, Sudarshan; Mokashi, Devdatta (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The current software systems are becoming complicated, heterogeneous and spread out making the task of code analysis a complicated task. The tools used in the traditional program analysis work independently, the statistical analysis, dynamic analysis, inspection of dependencies, vulnerability scanning, and quality assessment are commonly done separately. The result of this fragmentation is a lack of contextual knowledge, decreased explainability and inability to find root causes of defects or vulnerabilities. In order to overcome such shortcomings, the current paper suggests the creation of Opti-Blend, a visual graph-based modeling system of integrated code analysis. Opti-Blend converts several program representations, such as Abstract Syntax Trees (AST), Control Flow Graphs (CFG), Data Flow Graphs (DFG), Program Dependence Graphs (PDG) and Call Graphs, into a Hybrid Program Graph (HPG). The framework proposes a graph fusion mechanism to be used to combine multi-view representations to a semantic model. A query layer of visualization allows people to explain the issues and investigate them through the graph paths and dependencies. The suggested system can assist in defect detection, vulnerability, and code smell identification as well as dependency risk assessment all in a single visual setting. The experimental validation on open-source repositories proves to be a better detection tool and better traceability than individual tools. Opti-Blend is a contribution to a single, understandable and extendable modeling paradigm of next-generation integrated code intelligence systems.